Intensification of catfish cultivation at Pokdakan Baraya in Kotabatu Village, Bogor Regency - Hasanah, Uswatun; Kusumawardani, Linda Jati; Syahputri, Yulian; Mulyati, Ade Heri; Widiastuti, Diana; Warnasih, Siti (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2025)
Kotabatu Village, located in Bogor District, is home to several Fish Cultivator Groups (Pokdakan), one of which is Pokdakan Baraya, focused on cultivating catfish. Based on a focus group discussion conducted by the Pakuan University Implementation Team, Pokdakan Baraya faces challenges related to low income, high production costs, and the risks involved in traditional fish farming practices. In response, the team proposed the introduction of the Biofloc system for fish cultivation. The service methods included a comprehensive survey to assess the conditions and needs of the target community, followed by focus group discussions (FGD). The next phase involved outreach by the Pakuan University service team, employing knowledge-sharing methods, case studies, and training on the biofloc technology. To evaluate the impact, regular monitoring and evaluation processes were implemented, which included counseling, pond construction, seed distribution, nursery establishment, and intensive catfish rearing using the biofloc system. As a result of the biofloc system’s adoption, pond productivity increased by 1.8%, and the harvest time was reduced by 15 days. Additionally, the knowledge of Pokdakan Baraya members regarding fish cultivation technology grew by 60%, and their income saw an 81% increase from the sale of the catfish. The successful implementation of this system demonstrates significant improvements in the efficiency, productivity, and economic stability of the community.